2004
DOI: 10.1016/j.jacc.2003.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Optimal glycemic control is associated with a lower rate of target vessel revascularization in treated type II diabetic patients undergoing elective percutaneous coronary intervention

Abstract: In diabetic patients undergoing elective PCI, optimal glycemic control (A1c < or =7%) is associated with a lower rate of TVR, cardiac rehospitalization, and recurrent angina. These data suggest that aggressive treatment of DM to achieve A1c < or =7% is beneficial in improving the clinical outcome after PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(53 citation statements)
references
References 22 publications
2
48
0
3
Order By: Relevance
“…Although several studies have been reported on the relationship between glycemic control and outcomes after PCI in diabetic patients [6,13,14], it remains controversial. Hasdai et al [13] showed that the degree of glycemic control among diabetic patients did not have an impact on long-term outcomes after percutaneous coronary revascularization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although several studies have been reported on the relationship between glycemic control and outcomes after PCI in diabetic patients [6,13,14], it remains controversial. Hasdai et al [13] showed that the degree of glycemic control among diabetic patients did not have an impact on long-term outcomes after percutaneous coronary revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Hasdai et al [13] showed that the degree of glycemic control among diabetic patients did not have an impact on long-term outcomes after percutaneous coronary revascularization. Corpus et al [6] reported that optimal glycemic control was associated with a lower rate of TVR in diabetic patients undergoing PCI, and suggested that the aggressive treatment of diabetes mellitus was beneficial in improving the clinical outcome after PCI. Lemesle et al [14] reported that hemoglobin A1c was not a predictor of cardiac events after PCI with stent implantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose control is also an important factor in determining outcome following coronary intervention in people with diabetes. Corpus et al 10 studied 60 patients with diabetes and 179 patients without diabetes undergoing elective percutaneous coronary intervention. At 12 months, patients with diabetes and HbA1c >7% had a significantly higher rate of target vessel revascularisation compared with patients with diabetes and HbA1c <7% (34% vs 15%; p = 0.02).…”
Section: Glycaemia and Prevention Of Cardiovascular Eventsmentioning
confidence: 99%